(untitled) (Razão e Fé, 2026)
For Peter Abelard, sin is the contempt for God and the consent to evil. Considering the work Scito te Ipsum in its entirety, it is observed that it addresses the concepts of sin, intention, consent, and will. These concepts underpin and justify human actions. This issue led Abelard to reflect on the morality of reconciliation, which requires repentance, confession, and satisfaction. The philosopher positively qualifies repentance out of love for God. From this perspective, he distinguishes between a type of repentance driven by shame before society and another that is sincere. Intentionality is also involved in this matter because a fruitful penitence is one carried out with good intention, making repentance effective. Thus, since sin is the contempt for God that arises from consent, man can, through penitence, reconcile himself with his Creator.